Assessment of Health-Related Quality of Life for Patients with Inflammatory Bowel Diseases in Palestine - Smerat, Tasneem; Khdour, Maher; Abdoh, Qusay; Hallak, Hussein (Jordan Medical Journal, 2023)
Background: Inflammatory bowel disease (IBD) has a significant impact on quality of life (QoL). Disease activity has been suggested as an important indicator for QoL in patients with IBD. The aim of this study was to examine the association between disease activity and patient QoL. Methods: A correlation cross-sectional study was conducted from July 2017 to February 2018. We collected a convenience sample from three major hospitals in southern and northern Palestine. A disease-specific inflammatory bowel disease questionnaire (IBDQ) was used to examine QoL and the results were analyzed using SPSS version 20. Findings: 132 patients were involved in this study. The mean age was 34 years (SD 13) and 77 (58.3%) patients were men. Active disease had been reported in 81 participants (61.4%) in the previous six months. The average IBDQ scores were 150.72 ± 30.08. Emotional and bowel domains were more disrupted than other domains. Active disease was the major significant factor associated with IBD patients’ QoL in all-dimensional scores (p<0.001). Regression analysis revealed that patients in remission (r2 = 0.436, p<0.001), with high educational status (r2 =0.035, p=0.009) and using azathioprine (r2 =0.017, p=0.034) were independently associated with high QoL. Conclusions: This study showed a low QoL among Palestinian IBD patients compared to other countries, and identified a number of significant associated factors that should be considered when dealing with IBD.